2005
DOI: 10.1097/01.brs.0000167534.49069.e9
|View full text |Cite
|
Sign up to set email alerts
|

Center of Gravity and Radiographic Posture Analysis: A Preliminary Review of Adult Volunteers and Adult Patients Affected by Scoliosis

Abstract: The data analysis of offsets between the gravity line and radiographic parameters revealed a frontal plane mean displacement of the gravity line to the right. In the sagittal plane, a highly significant lack of correlation between the gravity line and plumbline was noted. The plumbline represents a common and convenient visual display of apparent sagittal plane imbalance, but its value as a marker of true postural balance must be questioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(51 citation statements)
references
References 14 publications
2
49
0
Order By: Relevance
“…Several clinical studies using a force plate have been performed to investigate the balance mechanism [42][43][44][45][46][47]. El Fegoun et al [43] reported a highly significant negative correlation between the gravity line and plumbline in the sagittal plane based on simultaneous assessment of fulllength freestanding spine radiographs and the floor projection of the center of pressure (gravity line), suggesting that the value of the plumbline as a marker of true postural balance must be questioned. We investigated balance using a force plate measurement during X-ray scanning and found that a representative balance parameter, ENV, had a tendency of positive correlation with PI-LL, suggesting that spino-pelvic mismatch affects not only the static sagittal alignment but also dynamic alignment, balance.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies using a force plate have been performed to investigate the balance mechanism [42][43][44][45][46][47]. El Fegoun et al [43] reported a highly significant negative correlation between the gravity line and plumbline in the sagittal plane based on simultaneous assessment of fulllength freestanding spine radiographs and the floor projection of the center of pressure (gravity line), suggesting that the value of the plumbline as a marker of true postural balance must be questioned. We investigated balance using a force plate measurement during X-ray scanning and found that a representative balance parameter, ENV, had a tendency of positive correlation with PI-LL, suggesting that spino-pelvic mismatch affects not only the static sagittal alignment but also dynamic alignment, balance.…”
Section: Discussionmentioning
confidence: 99%
“…However, no correlations were found between gravity line (GL) and C7 position by patients [6,7]. Gangnet et al [8] showed that the center of acoustic meati (CAM) remains near GL and proposed evaluating the distance from CAM to HA to quantify sagittal balance.…”
Section: Introductionmentioning
confidence: 99%
“…Antero-posterior (AP) and lateral (LAT) radiographs are commonly done but most studies evaluate posture only in the sagittal plane [10,11] although some authors report frontal values [6,12]. Simultaneous use of coronal and sagittal information was not found but in few studies [8,13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, differences in C7PL and GL positions have been demonstrated (GL -C7PL = 35.25 ± 19.4 mm): when the C7PL increased, no changes in GL position in relation to the heels were observed (the mean distance between GL and the heels was 111 mm). 7,22,31,40 Moreover, a poor correlation existed between C7PL and the true GL (r = 0.098; p < 0.3) 37 . In asymptomatic patients, GL is defined by a vertical line crossing the center of the mass of the entire body, which normally falls over the femoral heads and lies anterior to all vertebrae.…”
Section: 21mentioning
confidence: 99%